SUMO Conjugation Contributes to Immune Deviation in Nonobese Diabetic Mice by Suppressing c-Maf Transactivation of IL-4 - Leavenworth, Jianmei W. (2009)
It is not clear why the development of protective Th2 cells is poor in type 1 diabetes (T1D). c-Maf transactivates the IL-4 gene promoting Th2 cell development; therefore, abnormalities in c-Maf may contribute to reduced IL-4 production by CD4 cells from nonobese diabetic (NOD) mice. In this study we demonstrate that despite normal expression, c-Maf binds poorly to the IL-4 promoter (IL-4p) in NOD CD4 cells. Immunoblotting demonstrates that c-Maf can be modified at lysine 33 by SUMO-1 (small ubiquitin-like modifier 1). Sumoylation is facilitated by direct interaction with the E2-conjugating enzyme Ubc9 and increases following T cell stimulation. In transfected cells, sumoylation decreases c-Maf transactivation of IL-4p-driven luciferase reporter activity, reduces c-Maf binding to the IL-4p in chromatin immunoprecipitation assays, and enhances c-Maf localization into promyelocytic leukemia nuclear bodies. Sumoylation of c-Maf is increased in NOD CD4 cells as compared with CD4 cells from diabetes-resistant B10.D2 mice, suggesting that increased c-Maf sumoylation contributes to immune deviation in T1D by reducing c-Maf access to and transactivation of the IL-4 gene.